Studi Komparasi Layanan Pendukung Home Visit Di Sumatera Utara Dengan Malaysia: A Comparative Study of Home Visit Support Services in North Sumatra and Malaysia - Wahyuni Dazura; Ali Daud Hasibuan (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2025)
This study aims to determine the differences between the two countries. The results of this study are expected to provide useful information to improve the quality of guidance and counseling support services in Indonesia. The research method used is a qualitative method with a case study approach. The sample in this study were students of Al-Ulum Private Elementary School, Medan, North Sumatra, and students of Bandar Puteri Jaya National School, Sungai Petani, Kedah, with each school having 30 students. To collect accurate data in this study, three data collection techniques were used: observation, interviews, and documentation. The data analysis technique used in this study was triangulation, in which the researcher attempted to check the validity of the data by comparing the research data with the results of research conducted by other researchers. The results of the data analysis related to the comparative study of home visit support services at Al-Ulum Private Elementary School, Medan, North Sumatra, concluded that several things listed in the home visit activity report at Al-Ulum Private Elementary School, Medan, include the identity of the client (student), student problems, the process and results of the home visit, and the follow-up that has been given. In addition, documenting home visit reports is one of the efforts of guidance and counseling teachers to fulfill administrative requirements. Documentation is carried out so that all reports that have been prepared can be stored properly. This is done to maintain the existing data in the report. Meanwhile, the results of the data analysis related to the comparative study of home visit support services at Bandar Puteri Jaya National School, Sungai Petani, Kedah, showed that home visit services are very helpful in increasing student learning motivation and the benefits of this home visit service are that students and teachers are more optimal in delivering material and learning objectives are achieved optimally and teachers can handle students well. In addition, teachers also become aware of the student's family environment so that teachers can ask what obstacles to learning difficulties are by communicating with the student's parents so that teachers will find ways to solve student problems according to strategies that are suitable for the student themselves. This home visit service is very good to implement because during normal learning with a large number of students and active students, there will definitely be only a few others who are still afraid to ask questions and express their opinions, so with the home visit service with a small number of students, it provides an opportunity for inactive students to be trained to be more courageous in expressing their opinions.